Farnsworth's classical English style - Farnsworth, Ward, 1967- (Boston David R. Godine, Publisher, 2020)
"Farnsworth's Classical English Style is third in a series about principles of good writing, derived from an earlier age in the life of the language. While books on style usually emphasize some general principles, this book spends a lot of time on details, providing numerous examples of the principles Farnsworth outlines. Farnsworth asks why good writing sounds that way through many small choices in words, rhythm, and the construction of sentences and explains how those choices put force into writing and speech"--
Includes bibliographical references.
Keywords: English language -- Style